ARABIC LITERATURE IN THE ISLAMIC PERIOD: SYI’IR AND NATSAR - Wati, Ella Susila; Imawan, Yuli; Tiara, Hellen (Afshaha: Jurnal Bahasa dan Sastra Arab, 2023)
Arabic literature during the Islamic period played a crucial role, serving as a central force in shaping the Muslim community. This research aims to analyze the development of Arabic literature during the Islamic period (shadr Al-Islam) in the forms of syi’ir and natsar. It employs a qualitative descriptive research method with a literature review approach. Data were sourced from journals, books, notes, and other documents related to the development of Arabic literature during the Islamic period. Data were collected through documentation techniques and analyzed using qualitative data analysis methods, including data reduction, data presentation, and drawing conclusions. The research findings indicate that the development of Arabic literature during the Islamic period manifested in the forms of poetry and prose, both of which were present in two periods: the era of the Prophet and the era of the Rightly Guided Caliphs. The main characteristics include the use of language styles that constantly remind of Allah, containing verses of qauliyah and kauniyah. These literary works uphold the principles of amar ma’ruf nahi munkar, enjoining good and forbidding evil, marked by deep compassion and wisdom, reflecting Islamic teachings. The themes often revolve around profound love and devotion to Allah, the Prophet, parents, and dedication to struggles in the path of God. This love extends to encompass all of Allah's creations, reflecting a holistic and inclusive worldview